2020
DOI: 10.1186/s12872-020-01766-w
|View full text |Cite|
|
Sign up to set email alerts
|

Elderly patients with atrial fibrillation in routine clinical practice—peri-procedural management of edoxaban oral anticoagulation therapy is associated with a low risk of bleeding and thromboembolic complications: a subset analysis of the prospective, observational, multinational EMIT-AF study

Abstract: Background Annually > 10% of patients with atrial fibrillation on oral anticoagulation undergo invasive procedures. Optimal peri-procedural management of anticoagulation, as judged by major bleeding and thromboembolic events, especially in the elderly, is still debated. Methods Procedures from 1442 patients were evaluated. Peri-procedural edoxaban management was guided only by the experience of the attending physician. The primary safety outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Colonna et al 10 and Unverdorben et al 11 recently reported on the periprocedural management of edoxaban patients in the EMIT registries. Here, 123 of 280 cases (44%) undergoing high bleeding risk procedures had a preprocedural interruption <48 hours and 30 (11%) had an interruption longer than 72 hours.…”
Section: Edoxaban Management Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Colonna et al 10 and Unverdorben et al 11 recently reported on the periprocedural management of edoxaban patients in the EMIT registries. Here, 123 of 280 cases (44%) undergoing high bleeding risk procedures had a preprocedural interruption <48 hours and 30 (11%) had an interruption longer than 72 hours.…”
Section: Edoxaban Management Patternsmentioning
confidence: 99%
“…Unfortunately, cardiovascular events and mortality were not reported separately for patients undergoing major procedures. 18 The observational EMIT registries 10,11 followed SPAF and VTE patients with edoxaban in routine clinical care in a multinational setting and evaluated efficacy and safety in more than 1,000 patients undergoing a wide range of different procedures, including 280 major procedures. Similar to PAUSE, the EMIT registries showed higher rates of bleeding events in major compared with minor procedures (5.7 vs. 3.1%), although only five major events bleeding were documented in total (0.4% of all 1,155 procedures).…”
Section: Efficacy and Safety Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…After publication of the original article [ 1 ], the authors identified an error in Table 1 related to two values on EHRA bleeding risk-low row.…”
Section: Correction To: Bmc Cardiovasc Disord (2020) 20:504 101186/smentioning
confidence: 99%
“…Among the most frequently performed procedures are those requiring arterial and/or vascular access, such as coronary angiographies, percutaneous coronary interventions, valvular procedures, and ablations. 10 , 14 , 15 No clear evidence exists for the optimal time to interrupt or reinstate oral anticoagulation, balancing the reduction of MB against the potential higher risk of ischemic events, notably, thromboembolic stroke. It is also unclear which criteria physicians use to determine their periprocedural oral anticoagulation strategy and whether they would decide to use other antithrombotic agents during that interruption.…”
Section: Introductionmentioning
confidence: 99%